An Analytical Method to Estimate Groundwater Depletion of an Aquitard Due To Variable Drawdowns in Adjacent Aquifers. Issue 4 (30th March 2023) - Li, Zhaofeng; Li, Hao; Xiao, Xianxuan; Illman, Walter A.; Wang, Ruizhe; Zhang, Qiang
Abstract: Computing aquitard depletion, which is often overlooked, is of great significance for the assessment of groundwater resources and land subsidence. The issue is viewed as troublesome because of the additional computational burden, the poorly known hydrogeological parameters of the aquitard, and the lack of drawdown history in pumped aquifers. In this study, an analytical solution is derived to describe the drawdown variation in a nonlinear‐consolidated aquitard under the condition of variable drawdowns in adjacent aquifers. Based on the analytical solution, we study the characteristics of groundwater dynamics and water balance under the conditions of linearly increasing drawdown of aquifers in adjacent aquifers. In addition, we put forward a method to calculate the depletion and hydrogeological parameters of an aquitard corresponding to variable drawdowns in adjacent aquifers, applicable even when historical drawdown data are lacking. The accuracy of the method is generally very good, but results improve when the drawdown history of pumped aquifers is divided into more periods for estimation. Groundwater depletion of the aquitard increases with increasing compression index, coefficient of consolidation, thickness of aquitard, rate of drawdown change in the adjacent aquifer, while decreasing with initial void ratio, and initial effective stress. The proposed approach is demonstrated at a field site in Shanghai city of China, and it would help for the effective management of groundwater resources and estimation of the global transfer from groundwater to surface water. Key Points: Analytical solution of drawdown in an aquitard corresponding to variable drawdowns is derived An analytical method to estimate groundwater depletion from an aquitard is proposed Corresponding type‐curve fitting method is developed to estimate hydraulic parameters